A new case of interstitial 1q 25.3-32.1 deletion cytogenetic analysis molecular characterization and ultrasound findings - Libotte, Francesco (Journal of prenatal medicine, 2015)
INTRODUCTION: deletion of long arm of chromosome 1(1q-) is a rare condition. Clinical features include Dwarfism, severe mental retardation, microcephaly and short neck delineating the "intermediate 1q deletion syndrome"